THD Inspection of a Novel Envelop with a T Type (E-T) Multilevel Inverter with Reduced Switch Count - Rashmy Deepak; S Sumathi (Engineering Research: Perspectives on Recent Advances Vol. 5, 2025)
Modern-day switching has made inverters into complex circuitry with multiple levels. The overall power ratings of the inverters are improved by individual small powered devices. The unique structure of a multilevel inverter (MLI) synthesizes higher voltage levels with lower harmonics, without using transformers or series-connected synchronized switching devices. Multilevel inverters are a good choice for medium and low power applications. Multilevel inverters have found a wide place in the market for their good power quality output. This paper proposes a new Envelope with T type Novel Multilevel inverter with unequal sources and reduced switch count. The working principle of the circuit is explained. Firing angle calculations are done using a simple looping technique and later Genetic Algorithm is used to obtain optimum firing angles using the Selective Harmonic Elimination technique and improve the THD of the output voltage. Comparison is made between different types of inverters. The proposed E-T Type inverter circuit uses less number of semiconductor switches compared to previous circuits. Hence, it is concluded that the proposed inverter can be used for speed control of drives.